Knowledge and Attitude of Undergraduate Health Professions Students towards Hepatitis B and C - Ali Rashash R. Alzahrani (The Scientific World Journal)
The current study sought to establish the attitude and knowledge level of medical science students in Tibah University towards hepatitis B and C. A cross-sectional study involving 369 students drawn from the faculties of medicine, dentistry, applied medical sciences, pharmacy, nursing, and medical rehabilitation sciences was conducted where a standardised questionnaire was used to determine the attitude and knowledge level of undergraduate students drawn from the college of medicine in Tibah University, Saudi Arabia, regarding viral infections. With a mean of 0.71, 0.69, and 0.66 and a standard deviation (SD) of 0.24, 0.34, and 0.24 for virology and transmission, symptoms and clinical outcomes, and treatment and prevention, respectively, the knowledge level of the health professions students towards hepatitis B and C infections was significant. The knowledge level about the infections was higher among male students than among female students. Similarly, students in their final years of medical school had significantly higher knowledge levels about hepatitis B and C than their counterparts in their first years of medical school. There was also a positive correlation between the attitude of the health professions students towards the disease and their knowledge levels of the disease. Findings indicate that enhanced instruction on the nature, virology, transmission, symptoms, treatment, clinical outcomes, and prevention of hepatitis B and C can help improve the knowledge levels and attitude of the health professions students towards the disease and its management.